Features of the legal and military dimension of US foreign policy - Dmytro Lakishyk (Американська історія і політика, 2021)
The role of the United States in the security system of the global international space is difficult to overestimate. At the same time, the question of the degree to which America’s national security strategies are consistent with the requirements of international security is increasingly being questioned. On the one hand, the shift in emphasis to humanitarian values has made it more logical to use modern force to address issues such as the spread of WMD or genocide. On the other hand, the practice of American action in the Middle East and Central Asia has demonstrated the limits of power policy through the use of high technology in the use of traditional structures and strategies. The aim of the article is to analyze the transformational aspect of US security and defense policy, the impact of which becomes more significant than technological innovation.